The wake of iconoclasm: painting the church in the Dutch republic - Vanhaelen, Angela (Pennsylvania State University Press, 2012)
"Explores the relationship between art and religion after the iconoclasm of the Dutch Reformation. Reassesses Dutch realism and its pictorial strategies in relation to the religious and political diversity of the Dutch cities"--Provided by publisher